GC/MS Analysis of Volatile Compounds of the Essential Oil of Leaves of Ocimum sanctum Growing in Hisar, India - K. Suthar, Suresh; K. Malik, Ashok (Asian Journal of Chemistry, 2015)
Ocimum sanctum also addressed as Ocimum tenuiflorum is a sacred plant in Hindu culture and known as Tulsi in Hindi and Holy Basil in English. In this study, volatile constituents of Ocimum sanctum were extracted using hydrodistilation and their chemical constituents were identified and quantified by using GC-MS. Analysis of the essential oil have allowed to identify 13 components, but methyl chavicol (34.12 %), g-muurolene (32.44 %) and b-caryophyllene (24.33 %) are the main component of Ocimum sanctum.